Fetal development and the air pollution exposome: an integrative perspective of health pathways - Abarca-Castro, Eric Alonso; Reyes-Lagos, José Javier; Guzmán Ramos, Kioko; Montiel-Castro, Augusto J.; Arano-Varela, Hypatia; Mayer-Villa, Pablo Adolfo; Aguilar-Toalá, José Eleazar; Montesillo-Cedillo, José Luis; Talavera-Peña, Ana Karen (Frontiers in Cellular Neuroscience, 2025)
We offer an integrative perspective on how the air-pollution exposome shapes fetal development during the first 1,000 days and reverberates across mental health and behavior. Pregnant individuals and young children are disproportionately exposed to particulate matter (PM2.5), nitrogen dioxide (NO2), ozone (O3), and volatile organic compounds (VOCs) with social disadvantage amplifying risk. We bridge exposure to biology through three conduits. First, the placenta acts as a sensor and recorder, transducing signals that alter growth, immune tone, and neuroendocrine programming. Second, fetal autonomic control–captured by beat-to-beat fetal heart rate variability (fHRV) offers a relevant biomarker of neurodevelopmental integrity; the absence of direct ambient-pollution–fHRV studies is a pressing gap. Third, maternal immune activation, oxidative and endoplasmic reticulum (ER) stress, and disrupted morphogenesis reshape developing circuits, changes now traceable in utero by advanced fetal MRI. These pathways fit a developmental-programming frame: epigenetic remodeling, gene–environment interplay, endocrine-disrupting co-exposures, and gut-microbiome shifts create durable susceptibility. Clinically, the result is structural and functional brain alterations and child phenotypes spanning attention, executive control, affecting regulation, and learning, with clear pediatric and educational implications. We propose an exposome-based research agenda coupling high-resolution exposure assessment with placental molecular profiling, fetal/neonatal autonomic biomarkers (including fHRV), fetal/child neuroimaging, and longitudinal microbiome readouts in harmonized cohorts. In parallel, multisectoral actions–clean air urban design, targeted protection of pregnancy and early childhood, chemical regulation, and risk communication–should narrow exposure inequities while trials test biomarker-guided prevention. Aligning placental biology, autonomic metrics, and exposome science may transform risk stratification and safeguard the developing brain.